Insights into the systemic risk factors associated with diabetic retinopathy in the Indian population: A comprehensive systematic review and meta-analysis - KT Muhammed Favas; Mamidi Niveditha; Beema T Yoosuf; Manideep Bhukya; Parul Chawla Gupta; Pinaki Dutta; Dipika Bansal (Indian Journal of Ophthalmology)
Diabetic retinopathy (DR) is a predominant cause of vision impairment globally. Understanding risk factors is crucial for effective planning. The aim of this study is to comprehensively investigate the risk factors in the Indian population contributing to the increased incidence of DR, which is a potentially sight-threatening complication among diabetic individuals. A comprehensive literature search was done on PubMed, Embase, and Google Scholar databases for epidemiological studies reporting risk factors in the adult Indian population in the English language. Joanna Briggs Institute’s (JBI) critical appraisal tools were used to assess the quality of the included studies. Analysis was performed using R studio. I2 statistic was used for the assessment of heterogeneity. Results are expressed as odds ratio (OR) and standardized mean difference (SMD) along with a 95% confidence interval (CI). Overall, 20 studies enrolling 4,12,421 patients with 1,04,104 DR-positive and 3,08,317 DR-negative adults were analyzed. Being male (OR: 1.38, 95% CI: 1.11–1.72), intake of insulin (OR: 2.05, 95% CI: 1.02–4.14), higher HbA1c levels (MD: 0.50, 95% CI: 0.06–0.94), higher random (MD: 0.32, 95% CI: 0.10–0.55), and fasting blood glucose levels (MD: 0.51, 95% CI: 0.10–0.93) were found to be significantly associated with increased risks of DR among diabetic patients, while age, body mass index, hypertension, lipid profile, and smoking status did not indicate any association with DR. Good glycemic control remains the most important modifiable risk factor to reduce the risk of progression of DR and vision loss.